Heideggerian phenomenological hermeneutics: Working with the data - Smythe, Elizabeth (Nursing philosophy, 2020)
It is one thing to read about the methodology and methods of Heideggerian hermeneutic phenomenological research, the ontic description. It is quite another thing to be faced with an interview transcript. This article draws on a study that asked doctoral students about their experience of doing such research. How did they become "phenomenological/hermeneutic" in their thinking and writing? What helped them to find their way? We offer this article as a means of letting others learn from our own experiences. We support our insights with the writings of Heidegger and Gadamer to show the methodological congruence that is essential to Heideggerian phenomenological hermeneutic research.